Effect of interfacial coating and testing conditions on the flexural performance of carbon woven fibre-reinforced polyamide laminates. (7th February 2019) - Ma, Yan; Yu, Lichao; Jin, Shanshan; Zhao, Defang; Zhang, Songlin
ABSTRACT: This study addresses the effects of testing temperature and speed on carbon woven fibre-reinforced polyamide 6 composites (CF/PA6) with or without polyurethane dispersion (PUD) surface treatment. Dynamic mechanical analysis (DMA) was employed to check visco-elastic properties of CF/PA6 laminates. CF/PA6 laminates with and without surface treatment are tested and evaluated by three-point bending tests. Five testing temperatures (30°C, 60°C, 90°C, 120°C, 150°C) and three testing speeds (0.1, 1, 10 mm min −1 ) were chosen to investigate the time-temperature behaviour of CF/PA6 laminates. Results showed that PUD surface-treated CF/PA6 laminates exhibited better performance on mechanical properties but lower viscosity at various testing conditions owing to enhanced interfacial bonding capability.